Nilai Moral dalam Novel Bidadari Berbisik Karya Asma Nadia - Neka Nopendra; Sri Rahayu (UIR Press, 2022)
Moral actions are first based on the human heart itself. If the heart is not satisfied with what it has, it will be done with actions, both right and wrong actions. The research on